2017
DOI: 10.1080/17843286.2017.1372244
|View full text |Cite
|
Sign up to set email alerts
|

Two years follow-up of an open-label pilot study of treatment with rituximab in patients with early diffuse cutaneous systemic sclerosis

Abstract: This is the first multicentre Belgian collaboration investigating potential efficacy of rituximab in early dcSSc. Rituximab appears to be safe and tolerable and it may have beneficial effects on skin involvement, on overall disease activity and on stabilization of internal organ status in early dcSSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 23 publications
1
39
1
3
Order By: Relevance
“…Despite the fatal burden associated with this condition, treatment options for SSc remain limited 4. Preliminary case-reports and series have suggested that rituximab, a chimeric monoclonal antibody targeting B cells, could improve skin and lung fibrosis in SSc 5–19. However, these studies were mostly limited by small samples sizes, lack of control arms, single centre designs, discrepancies in study designs and short durations of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fatal burden associated with this condition, treatment options for SSc remain limited 4. Preliminary case-reports and series have suggested that rituximab, a chimeric monoclonal antibody targeting B cells, could improve skin and lung fibrosis in SSc 5–19. However, these studies were mostly limited by small samples sizes, lack of control arms, single centre designs, discrepancies in study designs and short durations of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…There is no effective treatment for SSc as yet, even though several extensive clinical trials were investigated, for example. inhibition of β‐catenin signalling, inhibition of tyrosine kinase and B‐cell depletion . The several studies demonstrated that the contribution of B cell and T cell in SSc development and pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…inhibition of β‐catenin signalling, inhibition of tyrosine kinase and B‐cell depletion . The several studies demonstrated that the contribution of B cell and T cell in SSc development and pathogenesis. In addition to the acquired immunological reaction on SSc, the role of the innate immune system in the pathogenesis of SSc is now being increasingly recognized .…”
Section: Introductionmentioning
confidence: 99%
“…A small number of studies have evaluated the efficacy of rituximab (RTX) as overall disease therapy in SSc, with suggestions of efficacy in both the skin and the lung (75)(76)(77)(78)(79). An open-label randomized trial in 60 patients with dcSSc and ILD compared monthly pulses of CYC 500 mg/m 2 versus RTX 1,000 mg × 2 doses (80).…”
Section: Rituximabmentioning
confidence: 99%